Study of serum magnesium in acute coronary syndrome patients - Yusof, Zurkurnai; ldrose, Alzamani Mohammad (2005)
There had been many studies done in the past either in-vitro or clinically indicating the possible role that Magnesium may play in acute coronary syndrome.Many studies showed the presence of hypomagnesemia in coronary artery disease and also during the attack of myocardial infarct. However there is hardly any studies done on Magnesium done in Malaysia,none with regards to coronary artery disease or acute coronary syndrome.There is a need to know whether there is hypomagnesemia in Acute Coronary Syndrome in the local population.Knowledge on this will serve as a guide on future investigations,studies and treatment of Acute Coronary Syndrome or as an adjunct of ACS treatment.To ascertain whether there is a significant level of Mg deficiency among the Acute Coronary Syndrome patients in USM hospital.To justify Mg investigations as a routine investigation together with other electrolytes investigation like Na and K. To determine any differences of serum Magnesium between ACS subgroups: STEMI,UA and NSTEMI.To form a basis for further investigations regarding Magnesium treatment in ACS patients.